2015
DOI: 10.3177/jnsv.61.195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Calcium Supplementation on Bone Metabolism, Kidney Mineral Concentrations, and Kidney Function in Rats Fed a High-Phosphorus Diet

Abstract: A high-phosphorus (P) diet has several effects on calcium (Ca) and P metabolism. It increases parathyroid hormone (PTH) secretion (1, 2), which causes an increase in bone resorption and a decrease in bone mineral density (BMD) (3-5). Our previous study demonstrated that elevated PTH secretion from a high-P diet increases mRNA expression of the receptor activator of NF-kB ligand (RANKL), a mediator of osteoclastic bone resorption, resulting in increased osteoclastic bone resorption (4). Moreover, it is well kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
1
8
1
Order By: Relevance
“…Femur RANKL mRNA was increased with high dietary phosphorus in both younger and older mice, but the RANKL:OPG mRNA ratio was only increased in the old mice, suggesting that the effects of high dietary phosphorus on bone resorption are more pronounced with aging. In a second study, Katsumata et al (55) further investigated the effects and interaction between high dietary calcium and phosphorus on bone outcomes in rats. Rats were fed either adequate calcium (0.5%) or high calcium (1.0%) and either adequate phosphorus (0.3%) or high phosphorus (1.5%) in a 2×2 factorial design.…”
Section: High Dietary Phosphorus Intake Effects On Bone Healthmentioning
confidence: 99%
“…Femur RANKL mRNA was increased with high dietary phosphorus in both younger and older mice, but the RANKL:OPG mRNA ratio was only increased in the old mice, suggesting that the effects of high dietary phosphorus on bone resorption are more pronounced with aging. In a second study, Katsumata et al (55) further investigated the effects and interaction between high dietary calcium and phosphorus on bone outcomes in rats. Rats were fed either adequate calcium (0.5%) or high calcium (1.0%) and either adequate phosphorus (0.3%) or high phosphorus (1.5%) in a 2×2 factorial design.…”
Section: High Dietary Phosphorus Intake Effects On Bone Healthmentioning
confidence: 99%
“…However, HCD supplementation significantly increased SCa, bone Ca content and Ca/Ash, whilst bone loss of lumbar vertebrae in 5/6 Nx mice was ameliorated. A previous study indicated that dietary Ca supplementation inhibits RANKL-mediated osteoclastic bone resorption via the suppression of PTH (8). Thus, these findings suggest that HCD supplementation may increase bone Ca content and bone remodeling via inhibiting RANKL-induced bone resorption in 5/6 Nx mice.…”
Section: Discussionmentioning
confidence: 72%
“…Epidemiological studies have demonstrated that Ca supplementation has beneficial effects on bone mineral content and bone mineral density (BMD) (6,7). In rats, Ca supplementation prevented the bone loss and decline in kidney function induced by a high-P diet (8). Furthermore, a high calcium diet (HCD) increases bone mineral (Ca and P) content in high-fat diet-induced obese mice (9).…”
Section: Introductionmentioning
confidence: 99%
“…These pharmacologic therapies can also alter the phosphorus/calcium ratio. The reduction of phosphorus can alter the calcium absorption, while increased phosphorus concentrations can increase the oxidative stress as well as the hormonal balance between phosphates, calcium, and vitamin D. This might be conducive to adverse effects on mineral metabolism and increased bone loss [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Alkaline phosphatase and osteocalcin are both bone formation markers [50,51]. Bone alkaline phosphatase (ALP) regulates bone mineralization [51].…”
Section: Discussionmentioning
confidence: 99%